(untitled) (TAJ: Journal of Teachers Association, 2010)
The main objective of the study were to determine the common symptoms and signs, pattern of valve lesion and complications of mitral valvular disease in our population. Fifty patients of mitral valvular disease of rheumatic origin were evaluated in the Departments of Medicine and Cardiology of Rajshahi Medical college Hospital, Rajshahi. Breathlessness was the commonest symptom followed by palpitation, cough and fatigue. Commonly encountered signs of mitral valvular disease were tapping apex beat, loud first heart sound and diastolic murmur at mitral area. The signs of pulmonary hypertension were present in the majority of the patients at presentation. Atrial fibrillation was also quite common, though only a few having thromboembolic manifestations. Majority of the patients suffering from mitral valvular disease are poor. A number of patients receive the treatment of bronchial asthma and pulmonary tuberculosis for dyspnoea and haemoptysis respectively before the diagnosis of valvular heart disease is made. DOI: 10.3329/taj.v22i1.5028 TAJ 2009; 22(1): 101-105